Interactions of the 67 kDa laminin receptor and its precursor with laminin. Issue 2 (10th November 2009) - Fatehullah, Aliya; Doherty, Caroline; Pivato, Géraldine; Allen, George; Devine, Lynda; Nelson, John; Timson, David J.
Abstract : The 67LR (67 kDa laminin receptor) enables cells to interact with components of the extracellular matrix. The molecule is derived from the 37LRP (37 kDa laminin receptor precursor); however, the precise molecular mechanism of this conversion is unknown. Recombinant 37LRP, expressed in and purified from Escherichia coli, bound to human laminin in a SPR (surface plasmon resonance) experiment. 67LR isolated from human breast-cancer-derived cells in culture was also shown to bind to laminin by SPR. However, the kinetics of association are qualitatively different. 37LRP, but not 67LR, binds to heparan sulfate. The binding of 37LRP to heparan sulfate did not affect the interaction of 37LRP with laminin. In contrast, heparan sulfate reduces the extent of binding of laminin to 67LR. Taken together, these results show that 37LRP has some of the biological activities of 67LR, even prior to the conversion event. However, the conversion affects the sites of interaction with both laminin and heparan sulfate.